STRATEGI BAURAN PEMASARAN PERUSAHAAN MADU IBUN DI KOTA TANGERANG - Rahman, Naufal; Djuwendah, Endah; Heryanto, Mahra Arari; Fatimah, Sri (Universitas Galuh, 2023)
Honey is a natural sweet substance or comes from nectar and is produced by honey bees which has many health benefits. Indonesia has natural wealth and great potential for beekeeping because there are 6 out of 7 species of bees in the world so that the prospects for honey beekeeping are very profitable. Data from the Central Statistics Agency shows that honey production in Indonesia has increased from 51,338 liters in 2020 to 189,780 liters in 2021. High honey production is driven by the high demand for honey in Indonesia due to the COVID-19 pandemic. The Ibun honey company is one of the companies that offers genuine raw honey products, which can be seen from the marketing strategy of Ibun honey products, which cannot be separated from competition with other honey products. The aims of this study are: 1) To find out the performance of the agribusiness company Madu Ibun in Tangerang City; 2) Knowing the strengths, weaknesses, opportunities and threats of the Ibun Honey Company; 3) Formulate a marketing strategy for the Honey Ibun Company in Tangerang City. The research design used is qualitative research with a case study research design. The techniques and data analysis that were selected and used were descriptive analysis and SWOT matrix analysis and QSPM through interview sheets and questionnaires. The performance of the Madu Ibun company's agribusiness business includes the production process of beekeeping, honey harvesting, filtering and packaging as well as product marketing to consumers. Based on the results of the SWOT analysis matrix for the honey ibun company, the results of the marketing strategy for honey ibun are in quadrant I, namely the Strengths opportunities (S-O) strategy or an aggressive strategy as indicated by alternative strategies.